Differential expression of 10 sweetpotato peroxidases in response to sulfur dioxide, ozone, and ultraviolet radiation - Kim, Yun-Hee (Plant physiology and biochemistry : PPB, 2007)
Secretory class III plant peroxidase (POD, EC 1.11.1.7) is believed to function in diverse physiological processes, including responses to various environmental stresses. To understand the function of each POD in terms of air pollutants and UV radiation, changes in POD activity and expression of 10 POD genes isolated from cell cultures of sweetpotato (Ipomoea batatas) were investigated in the leaves of sweetpotato after treatment with sulfur dioxide (SO(2) 500ppb, 8h/day for 5 days), ozone (O(3) 200ppb, 8h/day for 6 days), and ultraviolet radiation (UV-B 0.6mWm(-2) for 24h, UV-C 0.16mWm(-2) for 24h). All treatments significantly reduced the PSII photosynthetic efficiency (F(v)/F(m)). POD-specific activities (units/mg protein) were increased in leaves treated with SO(2) and O(3) by 5.2- and 7.1-fold, respectively, compared to control leaves. UV-B and UV-C also increased POD activities by 3.0- and 2.4-fold, respectively. As determined by RT-PCR analysis, 10 POD genes showed differential expression patterns upon treatment with air pollutants and UV radiation. Among the POD genes, swpa1, swpa2, and swpa4 were strongly induced following each of the treatments. Interestingly, basic POD genes (swpb1, swpb2, and swpb3) were highly expressed following SO(2) treatment only, whereas neutral swpn1 was highly induced following O(3) treatment only. These results indicated that some specific POD isoenzymes might be specifically involved in the defense mechanism against oxidative stress induced by air pollutants and UV radiation in sweetpotato plants